PRIVATE HOSPITAL DEVELOPMENT STRATEGY: EXPLORING THE INFLUENCE TO ENHANCE PATIENT LOYALTY - Belda, Madeline; Irawan, Agustinus Purna (Graduate Program of Universitas Tarumanagara, 2024)
With a population exceeding 270 million, Indonesia faces significant healthcare challenges, particularly infectious diseases. Private hospitals play a crucial role, and patient loyalty is essential for their success. This study aims to contribute to hospital strategy development by understanding factors influencing patient loyalty to private hospitals in Indonesia. Specifically, it explores the relationships between hospital image, Word of Mouth (WoM), patient satisfaction, and loyalty. A quantitative, cross-sectional study was conducted in Jakarta from September to October 2023. Data was collected from 131 out of 156 respondents at a private hospital in Jakarta using a validated questionnaire. SmartPLS 4 was employed for analysis. Hospital image significantly influences patient loyalty directly and indirectly through patient satisfaction. Positive WoM has a significant impact on both patient satisfaction and loyalty. The study confirms the positive correlation between hospital image, patient satisfaction and loyalty. The study emphasizes the importance of building and maintaining a positive hospital image through effective marketing, active WoM management, and service quality improvement. Strategies focusing on these aspects are recommended to strengthen patient relationships, enhance reputation, and remain competitive in the challenging healthcare industry. Future research should delve into factors reinforcing patient loyalty, explore the impact of digital marketing strategies on hospital image, investigate variables moderating the relationship between positive WoM and patient satisfaction, and explore effective patient feedback management strategies focusing on information technology.